Solidarity and Individualism as Traits of The 20 th Century Child Huckleberry Fin, Holden Caulfield and Jean Louise Finch (Global Journal of Human-Social Science, 2021)
This article will focus on the importance of educational values instilled in youth characters of the Ninetieth and Twentieth century American Literature. This article pays close attention to the way in which children react in an environment with limited resources and most importantly, how substantial the role of education is, when faced with a severe lack of any other aids. By the end of this article, with the use of contrasting images, we shall see how young characters such as Lee Harper's Scout, Mark Twain's Huck and Tom, and Salinger's Holden, find themselves in rather difficult situations and how they operate in getting out of the presumably rather inconvenient condition. Questions such as: Does education play a valuable role assuming that one finds themselves in a situation with no material, emotional, or any other type of resources?; How the environment could affect the children and what is the peculiar nature of all these things?; will be of importance in trying to analyse how solidarity may be one important factor in overcoming the limited resources situations and how individualism may be a limiting factor under these circumstances.
Keywords: solidarity; individualism; environment; crisis; education; condition; resources